Acute Effects of Heat‐Not‐Burn, Electronic Vaping, and Traditional Tobacco Combustion Cigarettes: The Sapienza University of Rome‐Vascular Assessment of Proatherosclerotic Effects of Smoking (SUR‐VAPES) 2 Randomized Trial. Issue 6 (19th March 2019) - Biondi‐Zoccai, Giuseppe; Sciarretta, Sebastiano; Bullen, Christopher; Nocella, Cristina; Violi, Francesco; Loffredo, Lorenzo; Pignatelli, Pasquale; Perri, Ludovica; Peruzzi, Mariangela; Marullo, Antonino G.M.; De Falco, Elena; Chimenti, Isotta; et al.
Abstract : Background: Little clinical research on new‐generation heat‐not‐burn cigarettes (HNBC) in comparison with electronic vaping cigarettes (EVC) and traditional tobacco combustion cigarettes (TC) has been reported. We aimed to appraise the acute effects of single use of HNBC, EVC, and TC in healthy smokers. Methods and Results: This was an independent, cross‐over, randomized trial in 20 TC smokers, with allocation to different cycles of HNBC, EVC, and TC. All participants used all types of products, with an intercycle washout of 1 week. End points were oxidative stress, antioxidant reserve, platelet activation, flow‐mediated dilation, blood pressure, and satisfaction scores. Single use of any product led to an adverse impact on oxidative stress, antioxidant reserve, platelet function, flow‐mediated dilation, and blood pressure. HNBC had less impact than EVC and TC on soluble Nox2‐derived peptide (respectively, P =0.004 and 0.001), 8‐iso‐prostaglandin F2α‐III ( P =0.004 and <0.001), and vitamin E ( P =0.018 and 0.044). HNBC and EVC were equally less impactful than TCs on flow‐mediated dilation ( P =0.872 for HNBC versus EVC), H2 O2 ( P =0.522), H2 O2 breakdown activity ( P =0.091), soluble CD40 ligand ( P =0.849), and soluble P‐selectin ( P =0.821). The effect of HNBC and, to a lesser extent EVC, on blood pressure was less evident than that of TC, whereas HNBC appeared more satisfying than EVC (all P <0.05). Conclusions: Acute effects of HNBC, EVC, and TC are different on several oxidative stress, antioxidant reserve, platelet function, cardiovascular, and satisfaction dimensions, with TCs showing the most detrimental changes in clinically relevant features. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT03301129.